How do you evaluate the expression (2/3)^4/((2/3)^-5(2/3)^0) using the properties of indices?.

2 Answers
May 23, 2017

(2/3)^4/((2/3)^-5(2/3)^0)=(2/3)^9=512/19683

Explanation:

We can use here the identities

a^mxxa^n=a^((m+n)) and a^m/a^n=a^((m-n))

As such a^m/(a^na^p)=a^((m-n-p))

Hence (2/3)^4/((2/3)^-5(2/3)^0)

=(2/3)^((4-(-5)-0))

=(2/3)^((4+5))

=(2/3)^9

or 2^9/3^9=512/19683

May 23, 2017

2^9/3^9 = (2/3)^9

= 512/19683

Explanation:

There are four properties of indices (exponents) to consider here:

Raising factors to a power: color(blue)((xy)^m = x^m xx y^m)

A negative index: color(magenta)(1/x^-m = x^m)

Index of 0. color(lime)("Anything to power of 0 is equal to"1)" "(except 0^0)

Multiply law: same bases, add the indices: x^m xx x^n = x^(m+n)

color(blue)((2/3)^4)/(color(magenta)((2/3)^-5)color(lime)((2/3)^0)) = (color(blue)(2^4/3^4)xxcolor(magenta)((2/3)^5))/(color(lime)((1))

=2^4/3^4xx2^5/3^5

= 2^9/3^9

This can also be written as (2/3)^9

= 512/19683